Welcoming speeches of Scottish subjects during the great progress of King James I Stuart to Edinburgh in 1617 - K. D. Dzyubinskaya (Шаги)
This article analyzes the welcoming speeches made by Scottish intellectuals during the journey of James VI and I Stuart to Scotland in 1617. These speeches, composed by the intellectu als themselves, reﬂected Scottish renaissance ideas on the status of Scotland. On the one hand, through such adresses Scottish intellectuals obtained the possibility to communicate with the crown and to express their attitude to the union of the two crowns and the king’s desire to reform the Scottish church. The author of the article pays special attention to the fact that Scottish intellectuals acknowledged the union of Scotland and England but perceived it as a union of two autonomous kingdoms. Using narratives drawn from Scottish history, intellectuals depicted for King James VI and I Stuart the historical independence of Scotland from English kings and the freedom of the Scottish Kirk from the inﬂuence of Rome.On the other hand, King James VI and I Stuart himself was part of this intellectual Scottish community, acting as patron for universities, colleges, and the intellectual community itself. In conclusion we notice that the welcoming speeches were similar in their content, depicting the glorious history of Scotland with the aim to extol Scottish culture and their Scottish King James VI and I Stuart.